2008
DOI: 10.1016/j.rapm.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Isobolographic Analysis of Epinephrine With Bupivacaine, Dextromethorphan, 3-Methoxymorphinan, or Dextrorphan on Infiltrative Anesthesia in Rats: Dose-Response Studies

Abstract: Epinephrine, dextromethorphan, 3-methoxymorphinan, and dextrorphan are known to have local anesthetic effects as infiltrative cutaneous analgesia in rats. Epinephrine increased the potency of bupivacaine, but not dextromethorphan, 3-methoxymorphinan, or dextrorphan as an infiltrative anesthetic. The cutaneous analgesic effects of adding epinephrine to dextromethorphan, 3-methoxymorphinan, or dextrorphan, are similar to combinations of 2 local anesthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…channel blockers. 2 They both produce spinal anesthesia, 3 sciatic nerve blockade, 4 and infiltrative cutaneous anesthesia 5,6 in rats. We found that dextromethorphan and dextrorphan, as local anesthetics, were more potent than lidocaine, 5 and the spinal blockade caused by dextrorphan was similar to that of bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…channel blockers. 2 They both produce spinal anesthesia, 3 sciatic nerve blockade, 4 and infiltrative cutaneous anesthesia 5,6 in rats. We found that dextromethorphan and dextrorphan, as local anesthetics, were more potent than lidocaine, 5 and the spinal blockade caused by dextrorphan was similar to that of bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous injections of drugs were administered as reported previously. 5,6,15 Briefly, the drugs, which were dissolved in normal saline 0.6 mL, were injected subcutaneously in non-anesthetized rats using a 30-G needle on the dorsal surface of the thoracolumbar region. The back of each rat was divided into left and right parts, either of which received one drug injection with a washout period of one week.…”
Section: Part I -Infiltrative Cutaneous Anesthesiamentioning
confidence: 99%
See 3 more Smart Citations